1999
DOI: 10.1103/physrevb.59.11755
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle x-ray-scattering study of phase separation and crystallization in the bulk amorphousMg62Cu25et al.

Abstract: We report on a small-angle x-ray-scattering ͑SAXS͒ and differential scanning calorimetry study of phase separation and crystallization in rapidly quenched amorphous Mg 62 Cu 25 Y 10 Li 3 alloy samples. Differential scanning calorimetry demonstrates the occurrence of crystallization and grain growth upon isothermal annealing of these samples at 135°C. The SAXS studies show the presence of large inhomogeneities even in the rapidly quenched as-prepared Mg 62 Cu 25 Y 10 Li 3 alloy that is attributed to phase separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…[54,55] In this context it was found, that the stabilization of the quasicrystalline shortrange order strongly depends on the concentration of dissolved oxygen in the melt. [56,57] (c) Two phase amorphous-composites: Such composites can be obtained by liquid phase separation during solidification, which has already been reported a long time ago in PdAu-Si [80] and in Pd-Ni-P. [81] Phase separation occurs in some metallic glasses during annealing in the supercooled liquid region prior to crystallization, as observed for Vitreloy 1 (Zr 41.25 Nb 13.75 Cu 12.5 Ni 10 Be 22.5 ) [82] and for Mg 62 Cu 25 Y 10 Li 3 ribbons [83] or during casting. [84][85][86][87][88][89][90][91][92][93] This behavior can be explained either as a precursor step before primary crystallization [82] or as a result of a positive enthalpy of mixing between the constituent elements.…”
Section: Reviewsmentioning
confidence: 63%
“…[54,55] In this context it was found, that the stabilization of the quasicrystalline shortrange order strongly depends on the concentration of dissolved oxygen in the melt. [56,57] (c) Two phase amorphous-composites: Such composites can be obtained by liquid phase separation during solidification, which has already been reported a long time ago in PdAu-Si [80] and in Pd-Ni-P. [81] Phase separation occurs in some metallic glasses during annealing in the supercooled liquid region prior to crystallization, as observed for Vitreloy 1 (Zr 41.25 Nb 13.75 Cu 12.5 Ni 10 Be 22.5 ) [82] and for Mg 62 Cu 25 Y 10 Li 3 ribbons [83] or during casting. [84][85][86][87][88][89][90][91][92][93] This behavior can be explained either as a precursor step before primary crystallization [82] or as a result of a positive enthalpy of mixing between the constituent elements.…”
Section: Reviewsmentioning
confidence: 63%
“…Figure 1 depicts a collection of SANS and SAXS data (taken from [14][15][16] and references in [11]) in a log-log plot of SðkÞ vs. k together with model functions (15) with n ¼ 3 and n ¼ 4. The plot outlines Fig.…”
Section: Gðrþmentioning
confidence: 99%
“…The plots for amorphous SiO 2 , the amorphous polymers PMMA, PET, PS, PE, Polycarbonate, the epoxy resins EPON 828 TETA, EPON 828 NMA, EPON 812, measured by SAXS, are taken from references in [11]. In the case of rapidly quenched amorphous Mg 62 Cu 25 Y 10 Li 3 alloy, measured by SAXS, the data of the as-prepared sample are presented (taken from [16]). In the SANS-measured 10 mol% Cu-Al 2 O 3 the formation of a-Al 2 O 3 has occured [14].…”
Section: Gðrþmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] It is found that the crystallization process is sensitive to alloy composition, 4 applied pressure, [5][6][7][8][9][10] annealing temperature, 11,12 and heating rate 13 so on. Schroers et al 13 has proved that a rate of about 200 K/s upon heating can avoid any crystallization events in the Zr 41 Ti 14 Cu 12.5 Ni 10 Be 22.5 bulk metallic glass.…”
Section: Introductionmentioning
confidence: 99%